2019
DOI: 10.3390/met10010023
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Fatigue of Unicone, Navigator Evo and Protaper Next Files in Reciprocate and Continuous Rotary Systems in Simulated Curved Canals—An In Vitro Study

Abstract: This study investigated the cyclic fatigue resistance of three brands of nickel-titanium rotary files—Unicone (size 25 0.06; Medin), Navigator Evo (W-4; size 25 0.06; Medin) and Protaper Next (X2; size 25 0.06 Dentsply Tulsa Dental)—in reciprocating and continuous motion, during artificial canal instrumentation. Seventy-two samples—Unicone (n = 24), Navigator Evo (n = 24), and Protaper Next (n = 24)—each measuring 25 mm in length, were allocated to reciprocating (n = 36) and continuous motion (n = 36) experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
2
0
0
Order By: Relevance
“…The present study fractured fragment length of the RP corresponded with the maximum flexural point of the artificial canal; however, fractures occurred more apically in the remaining groups. Previous studies indicated difference in the fractured fragment length when the instruments were operated with different kinematics or the curvature area was located more apically or the tip diameter [21, 22]. The results of our study are consistent with those of these studies [21, 22].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study fractured fragment length of the RP corresponded with the maximum flexural point of the artificial canal; however, fractures occurred more apically in the remaining groups. Previous studies indicated difference in the fractured fragment length when the instruments were operated with different kinematics or the curvature area was located more apically or the tip diameter [21, 22]. The results of our study are consistent with those of these studies [21, 22].…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies indicated difference in the fractured fragment length when the instruments were operated with different kinematics or the curvature area was located more apically or the tip diameter [21, 22]. The results of our study are consistent with those of these studies [21, 22].…”
Section: Discussionsupporting
confidence: 92%